The mediating sex-specific effect of psychological distress on the relationship between adverse childhood experiences and current smoking among adults - Strine Tara W; Edwards Valerie J; Dube Shanta R; Wagenfeld Morton; Dhingra Satvinder; Prehn Angela; Rasmussen Sandra; McKnight-Eily Lela; Croft Janet B (BMC, 2012)
Abstract Background Research suggests that ACEs have a long-term impact on the behavioral, emotional, and cognitive development of children. These disruptions can lead to adoption of unhealthy coping behaviors throughout the lifespan. The present study sought to examine psychological distress as a potential mediator of sex-specific associations between adverse childhood experiences (ACEs) and adult smoking. Method Data from 7,210 Kaiser-Permanente members in San Diego California collected between April and October 1997 were used. Results Among women, psychological distress mediated a significant portion of the association between ACEs and smoking (21% for emotional abuse, 16% for physical abuse, 15% for physical neglect, 10% for parental separation or divorce). Among men, the associations between ACEs and smoking were not significant. Conclusions These findings suggest that for women, current smoking cessation strategies may benefit from understanding the potential role of childhood trauma.